Communication Strategy Design based on the use of Social Networks in order to promote alternative Tourism with indigenous identity - Hernández Morales, Imelda (2013)
The intention of this work is to present the design and implementation of a communication strategy based on the use of social networks on the web 2.0, in order to promote alternative tourism with indigenous identity. This project has been developed by students of the majors in Communication, Marketing, and Animation and Digital Art, under the coordination of two professors of the Tecnológico de Monterrey, Campus Cuernavaca, who have applied the pedagogic model known as Learning - Service.